Immunogenic Cell Death Activates the Tumor Immune Microenvironment to Boost the Immunotherapy Efficiency - Li, Zhilin; Lai, Xiaoqin; Fu, Shiqin; Ren, Long; Cai, Hao; Zhang, Hu; Gu, Zhongwei; Ma, Xuelei; Luo, Kui (Advanced science, 2022)
Tumor immunotherapy is only effective in a fraction of patients due to a low response rate and severe side effects, and these challenges of immunotherapy in clinics can be addressed through induction of immunogenic cell death (ICD). ICD is elicited from many antitumor therapies to release danger associated molecular patterns (DAMPs) and tumor‐associated antigens to facilitate maturation of dendritic cells (DCs) and infiltration of cytotoxic T lymphocytes (CTLs). The process can reverse the tumor immunosuppressive microenvironment to improve the sensitivity of immunotherapy. Nanostructure‐based drug delivery systems (NDDSs) are explored to induce ICD by incorporating therapeutic molecules for chemotherapy, photosensitizers (PSs) for photodynamic therapy (PDT), photothermal conversion agents for photothermal therapy (PTT), and radiosensitizers for radiotherapy (RT). These NDDSs can release loaded agents at a right dose in the right place at the right time, resulting in greater effectiveness and lower toxicity. Immunotherapeutic agents can also be combined with these NDDSs to achieve the synergic antitumor effect in a multi‐modality therapeutic approach. In this review, NDDSs are harnessed to load multiple agents to induce ICD by chemotherapy, PDT, PTT, and RT in combination of immunotherapy to promote the therapeutic effect and reduce side effects associated with cancer treatment. This review summarizes the nanostructure‐based drug delivery systems‐based immunogenic cell death (ICD) induction approaches combined with immunotherapy. Engineered and functionalized NDDSs to enhance their delivery efficiency and activate the tumor immune microenvironment for improving immunotherapeutic efficiency are illustrated.